2011
DOI: 10.1007/s00192-011-1565-2
|View full text |Cite
|
Sign up to set email alerts
|

The value of preoperative urodynamics according to gynecologists and urologists with special interest in stress urinary incontinence

Abstract: Introduction and hypothesisThe aim of this study is to assess variations in practice in the use of preoperative urodynamics in women with stress urinary incontinence (SUI).MethodsWe performed an E-survey among all Dutch gynecologists and urologists who have SUI as focus in daily practice. The questions concerned the common policy and preferred policy. Descriptive statistics were used.ResultsOf the 260 targeted specialists, 163 (63%) responded. We found that 37% of the respondents performed standard preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…Interestingly, a Dutch survey in 2011 completed by gynaecologists (n = 103) and urologists (n = 60) representing 80 hospitals, has shown that only 37% performed urodynamics as part of routine investigation prior to SUI surgery, while 88% stated that a positive stress test during clinical examination would be sufficient for them to proceed with surgery. In this review, the commonest indications for urodynamics prior to surgery were symptoms indicating possible DO such as urgency [37]. Another survey in 2012 of gynaecologists (n = 400) and urogynaecologists (n = 200) conducted in the UK showed that the majority of surgeons agreed that urinary diary (95.8%), free uroflowmetry (94.2%), multichannel subtraction filling cystometry (99.5%), and voiding cystometry (98%) should be amongst the tools for UI assessment when contemplating secondary surgery [38].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, a Dutch survey in 2011 completed by gynaecologists (n = 103) and urologists (n = 60) representing 80 hospitals, has shown that only 37% performed urodynamics as part of routine investigation prior to SUI surgery, while 88% stated that a positive stress test during clinical examination would be sufficient for them to proceed with surgery. In this review, the commonest indications for urodynamics prior to surgery were symptoms indicating possible DO such as urgency [37]. Another survey in 2012 of gynaecologists (n = 400) and urogynaecologists (n = 200) conducted in the UK showed that the majority of surgeons agreed that urinary diary (95.8%), free uroflowmetry (94.2%), multichannel subtraction filling cystometry (99.5%), and voiding cystometry (98%) should be amongst the tools for UI assessment when contemplating secondary surgery [38].…”
Section: Discussionmentioning
confidence: 98%
“…80% of them indicated that they would operate on a patient with a positive stress test without urodynamics SUI, whereas only 21% would do this also in case the clinical stress test was negative. Many would not undertake primary surgical treatment when pre-operative DO is found 6 .…”
Section: For Pre-operative Urodynamicsmentioning
confidence: 99%
“…However, recent evidence‐based recommendations for the treatment of stress incontinence did not utilize intrinsic sphincter deficiency and bladder neck hypermobility as primary determinants in the selection of the type of sling . Furthermore, in a survey among gynecologists and urologist, treating SUI in daily practice, we found that only 9% of the specialists differentiate in the choice of sling on measurement of the closure mechanism . The majority of specialists apply only one type of sling procedure, which is possibly due to surgeon's experience and familiarity with that specific type.…”
mentioning
confidence: 95%